EFEKTIVITAS PENGAWETAN SECARA OZONISASI DAN IDENTIFIKASI TERHADAP KONTAMINASI KAPANG PADA KACANG TANAH (Arachis hypogaea L.) - Syawal Nurangga Kodhatin; Endang Kusdiyantini; Arina Tri Lunggani (Jurnal Akademika Biologi, 2014)
Peanut (Arachis hypogaea L.) is a potential plant protein source with a relatively cheap price, so that it can be consumed by almost all the community. Post-harvest handling of peanuts especially at the stage of the marketing needs to be done properly, because improper treatment can lead to contamination by fungi. As a result, it can reduce the quantity and quality of the product and can endanger the health of consumers. This study aims to determine the Ozonisation Preservation and Identification of Mold Contamination In Peanuts. Mold was isolated using the direct method (direct method) and dilution. Identification of molds were done macroscopically and microscopically. Identification was done by using Potato Dextrose Agar (PDA) and Malt Extract agar (MEA) as selective media. The result of Ozonisation Preservation with 3.5 ppm concentration showed that peanuts that had been exposed with ozone on first day containing the amount of molds lower than on the day 7, 14, 21, and 28. The result of mold identification on peanuts consisted of one genus Aspergillus with predominant isolate was A. flavus as many as 25 colonies. Keywords: peanut (Arachis hypogaea L.), ozonation, identification, mold